2009
DOI: 10.1016/j.mcn.2008.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Sensorimotor enhancement in mouse mutants lacking the Purkinje cell-specific Gi/o modulator, Pcp2(L7)

Abstract: Pcp2(L7) is a GoLoco domain protein specifically and abundantly expressed in cerebellar Purkinje cells. It has been hypothesized to "tune" Gi/o-coupled receptor modulation of physiological effectors, including the P-type Ca 2+ channel. We have analyzed a mouse mutant in which the Pcp2(L7) gene was inactivated and find significant anatomical, behavioral and electrophysiological changes. Anatomically, we observed mild cerebellar hypoplasia. Behaviorally, the mutants were altered in modalities atypical for a trad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
34
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(45 citation statements)
references
References 79 publications
11
34
0
Order By: Relevance
“…ProTa-related transgenic mice. Most interestingly, stronger ProTa signals that were found in neurons in Purkinje cell layer of cerebellum play an important role in movement, posture, and cognitive functions (Jorntell and Hansel 2006;Iscru et al 2009). In this study we successfully demonstrated the cell type-specific sub-cellular localization of ProTa in adult brain.…”
Section: Discussionmentioning
confidence: 99%
“…ProTa-related transgenic mice. Most interestingly, stronger ProTa signals that were found in neurons in Purkinje cell layer of cerebellum play an important role in movement, posture, and cognitive functions (Jorntell and Hansel 2006;Iscru et al 2009). In this study we successfully demonstrated the cell type-specific sub-cellular localization of ProTa in adult brain.…”
Section: Discussionmentioning
confidence: 99%
“…Some of these molecules display highly restricted and complex parasagittal patterns. Examples are aldolase C/zebrin II [46], gene transcription factors [41,47], intracellular signaling molecules (CaBP, cGK [48]; Pcp2/L7 [49][50][51]); ephrins, and Eph receptors [47,52]; and members of the cadherin superfamily (see below).…”
Section: Cadherins At Intermediate Stages Of Cerebellar Cortical Devementioning
confidence: 99%
“…On the other hand, it may be that Pcp2 is important for certain currently unidentified roles. Indeed, some evidence of this has already been reported (Xu et al, 2008;Iscru et al, 2009).…”
Section: Discussionmentioning
confidence: 69%
“…Detailed behavioral studies showed these mutants to possess enhanced motor learning abilities (Iscru et al, 2009).…”
Section: Introductionmentioning
confidence: 99%